Pengaruh Disiplin Kerja dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan PT. Cahaya Putera Kerinci Riau - Ahmad Fauzi; Sehani Sehani (Yayasan Almanar Pujud, 2026)
The goal of Human Resource Management (HRM) is to effectively manage the human element, ultimately leading to employee job satisfaction, both within the organization and the company. The objectives of this study are: 1) To determine the partial effect of work discipline on employee performance at PT Cahaya Putera Kerinci Riau, 2) To determine the partial effect of the physical work environment on employee performance at PT Cahaya Putera Kerinci Riau, and 3) To determine the simultaneous effect of work discipline and the physical work environment on employee performance at PT Cahaya Putera Kerinci Riau. The research method used was quantitative research. The results showed that 1) Work discipline has a positive and significant effect on employee performance at PT Cahaya Putera Kerinci Riau. 2) The physical work environment has a positive and significant impact on employee performance at PT Cahaya Putera Kerinci Riau. 3) Work discipline and the physical work environment jointly have a positive and significant impact on employee performance at PT Cahaya Putera Kerinci Riau.